2014
DOI: 10.1155/2014/263058
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-Antioxidant Balance during On-Pump Coronary Artery Bypass Grafting

Abstract: Backround. The aim of this study was to evaluate the changes in perioperative oxidant-antioxidant balance in ONCABG. Methods. Twenty-three patients were included in this study. Serum total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) values were assessed preoperatively, at 20 minutes after aortic clamping and at 30 minutes, 6 hours, and 48 hours after declamping (reperfusion). The patients were divided into 2 groups according to the median aortic cross clamping (XC) ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 16 publications
2
24
0
2
Order By: Relevance
“…Previous studies revealed that the increase in total peroxide, 8-isoprostane, nitrite-nitrate levels, and oxidative stress caused by the cross clamp period in CABG patients were correlated [22]. Again, in the study of Mentese et al [19], it was found that the oxidant/antioxidant balance was not affected in ONCABG patients having short cross clamp periods (29 minutes). CPB is correlated with the formation of ROS production and oxidative stress [2].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies revealed that the increase in total peroxide, 8-isoprostane, nitrite-nitrate levels, and oxidative stress caused by the cross clamp period in CABG patients were correlated [22]. Again, in the study of Mentese et al [19], it was found that the oxidant/antioxidant balance was not affected in ONCABG patients having short cross clamp periods (29 minutes). CPB is correlated with the formation of ROS production and oxidative stress [2].…”
Section: Resultsmentioning
confidence: 93%
“…CABG induces the excessive production of ROS such as hydroxyl, hydrogen peroxide, hypochlorite, and superoxide from various enzymatic and cellular sources [3]. In the study of Mentese et al [19] the increase in ROS was observed in ONCABG patients. Despite a significant increase in GSH level and CAT, GPx, and SOD activities in postoperative period, significant inhibition of increase in MDA in postoperative period was not shown in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanation for the primary mechanisms causing systemic inflammatory response (SIR) and oxidative stress during cardiac surgery includes the exposure of blood to synthetic material of ECC systems, the surgical trauma itself, and the sudden temperature changes of the body [8]. The close connection between ROS production, unphysiological circulation, and SIR during CPB is very well-known both with coated and noncoated ECC systems [13, 14]. Current studies have described the status of oxidative burden and the time course of their formation during CPB [15].…”
Section: Discussionmentioning
confidence: 99%
“…These are all sources of ROS production which will ultimately lead to depletion of plasma antioxidants. Coronary artery bypass surgery under CPB may possess an elevation in oxidant status and accordingly to this increase may raise antioxidant status [14]. …”
Section: Discussionmentioning
confidence: 99%